IVT-free, chemically synthesized protein-encoding RNA oligonucleotides for rapid production of personalized cancer vaccines - Qian Pan; Chi Zhang; Xinyue Wang; Jie Yin; Shengnan She; Xi Chen; Ruitao Dong; Ying Wu; Xinyuan Liao; Yanyan Wang; Hui Yan; Haomeng Kou; et al. (Proceedings of the National Academy of Sciences, 2026)
Personalized mRNA neoantigen vaccines demonstrate great potential in cancer therapy, but their customization typically requires more than three months, risking the loss of the optimal therapeutic window for patients. This delay is primarily due to the reliance of current mRNA vaccine production on plasmid fermentation and in vitro transcription (IVT), which involve multiple complex steps. Chemically synthesized RNA oligonucleotides, such as antisense oligonucleotides (ASOs), are produced sparing DNA templates or IVT, thus enabling rapid manufacturing. However, ASOs are limited in length, which precludes their ability to encode proteins. Here, we introduced a 39 nucleotides cap-independent translation enhancer (CITE) element termed BBV that can drive RNA translation. Furthermore, BBV was compatible with efficient rolling circle translation (RCT). We chemically synthesized RNA oligonucleotides containing BBV and gene of interest (GOI) with characteristic 5’-OH and 3’-P termini, which could undergo circularization by endogenous RtcB RNA ligases and efficiently encode proteins through RCT in mammalian cells. We designated these RNA oligonucleotides as Protein-Encoding RNA Oligonucleotides (PEOs). Notably, compared with IVT-produced RNAs, PEOs contained undetectable levels of proinflammatory double-stranded RNAs and exhibited minimal immunogenicity. We further demonstrated that PEO-OVA (encoding OVA antigens) significantly inhibited tumor growth comparable to mRNA vaccine. In an orthotopic glioma model, PEO vaccine also exhibited therapeutic benefits with checkpoint blockade therapy. This study establishes an IVT-free RNA vaccine platform that enables rapid, safe, and highly druggable manufacturing of personalized cancer vaccines, offering substantial potential for clinical application.